The terrestrial isopod fauna (Isopoda, Oniscidea) of Abrau Peninsula, north-west Caucasus, Russia - Daria M. Kuznetsova; Konstantin B. Gongalsky (ZooKeys)
From 2001 to 2022, the woodlice fauna of Abrau Peninsula, north-west Caucasus, Russia was examined. The collections yielded 5,581 specimens, which belong to 25 species, 19 genera, and 15 families. The most diverse families are Cylisticidae, Platyarthridae, Trachelipodidae, and Trichoniscidae, each with three species. The most diverse genera are Platyarthrus and Trachelipus. Five species have been noticed to the Russian fauna for the first time: Tylos europaeus, Acaeroplastes melanurus, Platyarthrus caudatus, Buddelundiella cataractae, and Armadillidium cf. marmoratum. The fauna of the Abrau Peninsula is predominantly Mediterranean and with a high percentage of endemics (12%). Further records are expected with more detailed studies of especially the family Trichoniscidae.